Convenor - Manganaris, George A. (My University, 2026)
V Postharvest Unlimited Conference was held in Cyprus during the period 10-13 June 2014, being considered by Dr. Peter Toivonen, ISHS representative, as the most successful ever carried out in this series. This was the first ISHS meeting ever held in Cyprus. Organization of this event was a joint initiative of the Cyprus University of Technology (CUT), Department of Agricultural Sciences, Biotechnology & Food Science and the Mediterranean Agronomic Institute of Chania, Greece. Conference was attended by 246 delegates and accompanying persons, derived from 43 different countries, while Conference website [www.cut.ac.cy/postharvest] received ca. 23,000 unique visits from over 160 countries.